Crushing strength of square hollow steel tubular sections externally jacketed by carbon fibre reinforced polymer strips. (2020) - Sivasankar, S.; Amudhavalli, N.K.; Praveen Kumar, A.; Shunmugasundaram, M.
Abstract: Square Hollow Steel (SHS) tubular sections have wide range of structural applications comprise of strength and ductility and therefore they are successfully performed in seismic regions. However they failed due to additional loads, faulty design and construction, severe environmental situation and corrosion. FRP technology provides better solution for the above mentioned problems compared to traditional methods. This paper presents the SHS tubular sections externally wrapped with CFRP sheets and subjected by axial crushing. Width and spacing of strips are kept constant and number of layers can be varied as one, two and three. After the crushing test, results were compared with one another and the wrapped specimen. Finally, failure pattern, stress-strain curve, axial crushing strength, load vs deformation curve and ductility were found from the test results and also suggested the optimum usage of CFRP strips for SHS strengthening.